Frailty and Perceived Financial Exploitation: Findings from the Finance, Cognition, and Health in Elders Study. (November 2020) - Axelrod, Jenna; Mosqueda, Laura; Weissberger, Gali H.; Nguyen, Annie L.; Boyle, Patricia A.; Parunakian, Emanuil; Han, S. Duke
Objective: Many older adults who are cognitively intact experience financial exploitation (FE), and the reasons for this are poorly understood.Methods: Data were gathered from 37 older adults ( M age = 69.51, M education = 15.89, 62% female) from the Finance, Cognition, and Health in Elders Study (FINCHES). Twenty-four older adults who self-reported FE were demographically-matched according to age, education, race, and MoCA performance to thirteen older adults who denied experiencing FE. Participants completed the Tilburg Frailty Inventory.Results: FE participants reported greater total frailty ( t = 2.06, p = .04) when compared to non-FE participants. Post-hoc analyses revealed that FE participants endorsed greater physical frailty ( U = 89, p = .03), specifically poorer sensory functioning (hearing and vision).Discussion: Findings suggest frailty is associated with FE in old age and may represent a target for intervention programs for the financial wellbeing of older adults.